The Exploitation of Migrant Workers in Atticus Lish's Novel Preparation for the Next Life (2014) - Arnold Setiawan; Leni Marlina (English Language and Literature, 2020)
This thesis is the analysis of a novel which written by Atticus Lish entitled Preparation for the Next Life (2014). It explores the issue of the exploitation of migrant workers which reflected by the main character and representation of migrant workers. It is also intended to find out the contribution of fictional devices such as character, plot (conflict), and setting in revealing the issue of the exploitation of migrant workers. This analysis related to the concept of exploitation and alienation which developed by Karl Marx that is supported by the text-based and context-based interpretation. The result of this analysis shows about the industrial owner acts of the exploitation of migrant workers. It can be seen in two ways, manipulating the managing systems and cutting wages.